Respirometric assessment of aerobic sludge stabilization - Tas, Didem Okutman (Elsevier BV, 2010)
Aerobic sludge stabilization was assessed respirometrically with the sludge taken from the secondary settling tank of a domestic wastewater treatment facility in Istanbul, Turkey. Zero-order removal rates of 178, 127 and 44 mg/L day were found for Suspended Solids (SS), Volatile Suspended Solids (VSS) and Total Organic Carbon (TOC) at the end of 18 days sludge stabilization, respectively. Significant nutrient release was observed by the mineralized nitrogen and phosphorus from the death and lysis of microorganisms. The model simulations for the batch respirometric assays for initial, 7th and 18th days of the stabilization agree reasonably well with the experimental data. The maximum storage rates (k(sto)) as well as maximum growth rates on stored products (micro(H2)) decrease with increasing stabilization period. Respirometric assays indicated the presence of microorganisms that started to compete with the dominant microorganisms as a result of the stabilization. As such, these findings have significance in terms of the efforts related to the sludge management and application processes.
Keywords: Sewage; Turkey; Nitrogen; Phosphorus; Models, Theoretical; Waste Disposal, Fluid; Carbon; Water Purification; Bacteria, Aerobic; Bioreactors; Oxygen Consumption